1997
DOI: 10.1021/jp971576m
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer Processes in Confined Systems. Nile Red in Reverse Micelles

Abstract: Intramolecular charge transfer (ICT) processes of the neutral fluorescence probe, nile red, I, confined in the water pool of aerosol-OT (AOT) reverse micelle in n-heptane, is studied using picosecond emission spectroscopy. Utilizing the solvatochromism of nile red, only those probe molecules inside the reverse micelle are selectively excited. It is observed that while in aqueous solutions the lifetime (τf) of nile red is 650 ps, inside the reverse micelles τf increases to 3.73 ns in reverse micelle and to 2.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
192
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(207 citation statements)
references
References 44 publications
13
192
1
1
Order By: Relevance
“…7,[13][14][15][16][17][18][19][20][21] As an example, Cho et al reported that ANS in reverse AOT micelles exhibited a double exponential decay: short component=0.3 -0.6 ns and long component=2.6 -5.1 ns at w 0 =4 -33.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,[13][14][15][16][17][18][19][20][21] As an example, Cho et al reported that ANS in reverse AOT micelles exhibited a double exponential decay: short component=0.3 -0.6 ns and long component=2.6 -5.1 ns at w 0 =4 -33.…”
Section: Fluorescence Dynamics Of Ans In Reverse Aot Micelles and Itsmentioning
confidence: 99%
“…As one of the several advantages of a reverse AOT micellar system, the size of the water pool can be controlled precisely at the nanometer level through the molar ratio of water to AOT: 7 Therefore, size effects on chemical and physical properties in nanometer dimensions can be studied by the use of reverse AOT micelles. Indeed, reverse AOT micelles have been studied by various techniques such as fluorescence spectroscopy [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , NMR 22,23 , ESR 24,25 , IR [26][27][28] , and so on. [29][30][31][32] These studies demonstrated that polarity [8][9][10] , viscosity 11 , pH 12 , and other properties 30,32 of the water pool in the micelles were different from those in the bulk state and were dependent on the w 0 value.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solvation dynamics of water and non-aqueous polar solvents in reverse micelles were demonstrated to depend on the molar ratio of solvent to surfactant [2,[10][11][12][13][14][15]. Shirota and Horie reported that the solvation dynamics were retarded by up to four orders of magnitude because of the presence of hydrogen-bonding network in reverse micelles [10].…”
Section: Introductionmentioning
confidence: 99%
“…We attribute the shortest lifetime t 1 to NR populations in a relatively hydrophilic micro-environment (corresponding to peak 3 from multi-peak fitting), possessing a lifetime close to the literature value of 0.650 ns for NR in aqueous buffer. 18 The slightly longer lifetime t 2 is attributed to NR populations that are bound to the various features mentioned above for peak 2, while the longest lifetime t 3 is attributed to NR molecules bound to viral membranes (peak 1 from multipeak fitting).…”
Section: Discussionmentioning
confidence: 92%